(untitled) (Asian Journal of Pharmaceutics (AJP), 2022)
This paper aims to explore primary health-care clinics in Saudi Arabia with a focus on patient behavior and adopting a healthy lifestyle. This is important, as the Saudi Health Information Survey shows an increased demand for health-care services due to the population growth rate in Saudi Arabia, as well as the impact of lifestyle diseases on the goals of the Ministry of Health and Vision 2030.